Take control of iOS & iPadOS privacy and security - Fleishman, Glenn (Take Control Books, 2022)
Master networking, privacy, and security for iOS and iPadOS! Version 2.1.1, updated January 17, 2022 Ensuring that your iPhone or iPad's data remains secure and in your control and that your private data remains private isn't a battle--if you know what boxes to check and how to configure iOS and iPadOS to your advantage. Take Control of iOS & iPadOS Privacy and Security takes you into the intricacies of Apple's choices when it comes to networking, data sharing, and encryption. Updated for iOS 15 and iPadOS 15! Your iPhone and iPad have become the center of your digital identity, and it's easy to lose track of all the ways in which Apple and other parties access your data legitimately--or without your full knowledge and consent. While Apple nearly always errs on the side of disclosure and permission, many other firms don't. This book comprehensively explains how to configure iOS 15 and iPadOS 15 to best protect your privacy while messaging, email, browsing, and much more, and how to ensure your devices and data are secure from intrusion. Take Control of iOS & iPadOS Privacy and Security covers how to configure the hundreds of privacy and data sharing settings Apple offers in iOS and iPadOS, and which it mediates for third-party apps. You'll learn how Safari has been increasingly hardened to protect your web surfing habits, personal data, and identity--particularly with the addition of the iCloud Private Relay, an option for iCloud+ subscribers to anonymize their Safari browsing. In addition to privacy and security, this book also teachers you everything you need to know about networking, whether you're using cellular, Wi-Fi, Bluetooth, or combinations of all of them, as well as about AirDrop, AirPlay, Airplane Mode, and Personal Hotspot and tethering. You'll learn how to: Master all the options for a Personal Hotspot for yourself and in a Family Sharing group. Troubleshoot problematic Wi-Fi connections. Set up a device securely from the moment you power up a new or newly restored iPhone or iPad. Manage Apple's new built-in second factor verification code generator for extra-secure website and app logins. Protect your email by using an address Apple manages and relays messages through for you. Understand Safari's blocking techniques and how to review websites' attempts to track you. Anticipate Apple's potentially privacy-challenging changes designed to improve the safety of children, both those using Apple hardware and those who suffering abuse. Optimize cellular data use to avoid throttling or overage charges, while always getting the best throughput. Understand why Apple might ask for your iPhone, iPad, or Mac password when you log in on a new device using two-factor authentication. Share a Wi-Fi password with nearby contacts and via a QR Code. Differentiate between encrypted data sessions and end-to-end encryption. Stream music and video to other devices with AirPlay 2. Deter brute-force cracking by relying on a USB Accessories timeout. Configure Bluetooth devices. Transfer files between iOS and macOS with AirDrop. Block creeps from iMessage, FaceTime, text messages, and phone calls. Secure your data in transit with a Virtual Private Network (VPN) connection. Protect Apple ID account and iCloud data from unwanted access.